Pengaruh Konseling Antenatal terhadap Tingkat Penerimaan IUD Pasca Salin:Non RCT - Andrianto Kurniawan; Risanto Siswosudarmo (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2019)
Background: Postpartum period is a period where a woman has a great motivation to use a contraceptive. The present data showed that the use of IUD was only about 7,75% of all mixed contraceptive use. Counseling carried out during the antenatal care period continued during early labor is believed be able to increase its acceptance. Objective: To compare the effect of antenatal counseling continued during the early labor versus counseling in the early labor only on the acceptance of postpartum IUD use.Method: The study was carried out in Sardjito Hospital and several Puskesmas in the province of Yogyakarta during six months period from January to June 2015. A non-randomized controlled trial (quasi experimental design) was used. Pregnant women meeting the inclusion and exclusion criteria that are counseled during their antenatal visit continued during their early labor were assigned as the exposed group. Those who are counseled during the early labor only were assigned to the control group. Counseling was done using a specific designed card introduced by BKKBN. The main outcome of interest is the real insertion of postpartum IUD. Chi square test, relative risk and logistic regression were used for statistical analysis.Result and Discussion: A total of 144 subjects were recruited consisting of 72 subjects as the exposed group and 72 as the control. Both groups were comparable in terms of age, parity, education, mode of delivery, and history of previous IUD use. The rate of IUD insertion on the exposed group was 52.8% compared to 26.4% in the control (RR 2.00; 95% CI 1.28-3.12). Other factors contributing to the acceptance of postpartum IUD were mode of delivery and previous IUD use. Logistic regression showed that the most dominant factor contributing to the acceptance of postpartum IUD was history of previous IUD use, (OR 8,42; 95% CI 1,68–42,27) followed by mode of delivery (OR 4.96; 95% CI 1.86–13.26), while timing of counseling was the third (RR 2.93; 95% CI 1.36–6.32).Conclusion: Counseling carried out during ANC continued in the period of early labor increased significantly the acceptance of postpartum IUD. Other factors contributing to the acceptance of IUD use were history of previous IUD use and mode of delivery.Key words: Postpartum IUD; Time of Counseling; Antenatal Care; Rate of Acceptance; IUD pasca salin; waktu konseling